Manajemen Risiko Terhadap Keamanan dan Keselamatan Wisatawan Pada Aktivitas Wisata Bahari di Tanjung Benoa, Kabupaten Badung (Jurnal Destinasi Pariwisata, 2025)
Tanjung Benoa Beach is a major marine tourism destination in Bali, offering various water sports activities such as parasailing, banana boat, and jet skiing. However, these water sports activities in Tanjung Benoa carry high risks of accidents, which may be caused by factors such as weather changes, wave currents, guide negligence, and equipment malfunction. This study aims to analyze the implementation of tourist safety in marine tourism activities at Tanjung Benoa, Badung Regency, focusing on risk management for tourist safety. The research method used is purposive sampling, with data collection through observation, in-depth interviews with water sports operators at 7 watersport providers, tourists, and relevant parties, as well as documentation studies on safety regulations and accident cases. The research findings show that there are 13 marine tourism activities provided by 7 water sports businesses in Tanjung Benoa, all conducted in accordance with standard operating procedures and under the supervision of instructors. The applied risk management includes hazard identification, risk assessment, and risk control. Identified risks include natural hazards, equipment malfunctions, and health issues among tourists. The risk assessment shows that most activities have high risks, with 54 activities categorized as extreme risk and 36 as high risk. Risk control measures include monitoring weather conditions, inspecting and maintaining equipment, providing insurance, and conducting health checks for tourists. Recommendations to minimize accidents include regular monitoring of environmental conditions, mandatory use of safety equipment, and first aid training for instructors.
Keywords: Risk Management; Tourist Safety; Tourist Security; Marine Tourism